Focal CA3 hippocampal subfield atrophy following LGI1 VGKC-complex antibody limbic encephalitis - Miller, Thomas D.; Chong, Trevor T.-J.; Aimola Davies, Anne M.; Ng, Tammy W.C.; Johnson, Michael R.; Irani, Sarosh R.; Vincent, Angela; Husain, Masud; Jacob, Saiju; Maddison, Paul; Kennard, Christopher; Gowland, Penny A.; et al. (Oxford Journals, 2017)
Magnetic resonance imaging has linked chronic voltage-gated potassium channel (VGKC) complex antibody-mediated limbic encephalitis with generalized hippocampal atrophy. However, autoantibodies bind to specific rodent hippocampal subfields. Here, human hippocampal subfield (subiculum, cornu ammonis 1-3, and dentate gyrus) targets of immunomodulation-treated LGI1 VGKC-complex antibody-mediated limbic encephalitis were investigated using in vivo ultra-high resolution (0.39 x 0.39 x 1.0 mm³) 7.0T magnetic resonance imaging [n = 18 patients, 17 patients (94%) positive for LGI1 antibody and one patient negative for LGI1/CASPR2 but positive for VGKC-complex antibodies, mean age: 64.0 ± 2.55 years, median 4 years post-limbic encephalitis onset; n = 18 controls]. First, hippocampal subfield quantitative morphometry indicated significant volume loss confined to bilateral CA3 [F(1,34) = 16.87, P < 0.0001], despite hyperintense signal evident in 5 of 18 patients on presentation. Second, early and later intervention (<3 versus >3 months from symptom onset) were associated with CA3 atrophy. Third, whole-brain voxel-by-voxel morphometry revealed no significant grey matter loss. Fourth, CA3 subfield atrophy was associated with severe episodic but not semantic amnesia for postmorbid autobiographical events that was predicted by variability in CA3 volume. The results raise important questions about the links with histopathology, the impact of the observed focal atrophy on other CA3-mediated reconstructive and episodic mechanisms, and the role of potential antibody-mediated pathogenicity as part of the pathophysiology cascade in humans.